Virtual Da'wah Through Youtube Channel: Communication Strategy of Koh Dennis Lim’s Content in Building Public Trust - Altruis Bizurai Chillyness; Luluk Fikri Zuhriyah (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
This study investigates the communication strategies employed by Koh Dennis Lim in his YouTube da’wah activities, focusing on how he builds public trust through digital platforms. Utilizing a qualitative approach, the research analyzes selected videos and viewer feedback to identify effective persuasive techniques. The findings reveal that Koh Dennis employs a combination of ethos, logos, and pathos to engage his audience. His use of historical narratives, personal testimonies, and relatable analogies fosters emotional connections and enhances credibility. The study highlights the importance of moderate positioning and audience inclusivity, demonstrating that effective da’wah can be achieved without confrontation. By creating a welcoming environment for dialogue, Koh Dennis successfully shifts the paradigm of Islamic preaching from a confrontational to a conversational approach. This research contributes to the understanding of modern religious communication, emphasizing the role of digital media in enhancing the reach and impact of religious messages. The implications of these findings suggest that a soft-power model of dawah is essential in today’s pluralistic society, where empathy and authenticity are crucial for building trust and fostering engagement.